Deskrypcja kąta szpotawości i koślawości piątego palca stóp dzieci i młodzieży w wieku od 4 do 18 lat w świetle mory projekcyjnej - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław. Deskrypcja kąta szpotawości i koślawości piątego palca stóp dzieci i młodzieży w wieku od 4 do 18 lat w świetle mory projekcyjnej = Description the varus and valgus angle on the fifth finger of the foot of children and youth aged 4 to 18 years in the light of the moiré projection. Journal of Education, Health and Sport. 2015;5(9):245-260. ISSN 2391-8306. DOI10.5281/zenodo.30538 http://dx.doi.org/10.5281/zenodo.30538 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A245-260 https://pbn.nauka.gov.pl/works/620061 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 06.09.2015. Deskrypcja kąta szpotawości i koślawości piątego palca stóp dzieci i młodzieży w wieku od 4 do 18 lat w świetle mory projekcyjnej Description the varus and valgus angle on the fifth finger of the foot of children and youth aged 4 to 18 years in the light of the moiré projection Mirosław Mrozkowiak Uniwersytet Kazimierza Wielkiego, Instytut Kultury Fizycznej Zdrowia i Turystyki w Bydgoszczy e-mail: magmar54@interia.pl strona: http://wadypostawy.republika.pl Słowa kluczowe: kąt szpotawości i koślawości palca V. Streszczenie Wstęp. Współczesny i ogólnie praktykowany tryb życia sukcesywnie ogranicza wysiłek fizyczny na rzecz sedenteryjnego modelu spędzania czasu wolnego. Destrukcyjny wpływ hipokinezy i obciążeń statycznych znajduje odzwierciedlenie w stawach kręgosłupa, barkowych, biodrowych i stóp, skutkując zaburzeniami morfologicznymi całego organizmu, bowiem zmiany te ze względy na jedność morfo-funkcjonalną całego narządu ruchu nie ograniczają się tylko do lokalnych zmian. Cel. Określenie kąta szpotawości lub koślawości palca piątego stóp w warunkach obciążenia masą własną kobiet i mężczyzn w wieku od 4 do 18 lat. Materiał i metodyka. Badaniami objęto populację 9804 kobiet i 8699 mężczyzn w wieku od 4 do 18 lat, z wybranych losowo przedszkoli i szkół regionu Warmińsko – Mazurskiego. Metodyka badań obejmowała pomiar kąta szpotawości lub koślawości piątego palca stóp. Do oceny wykorzystano stanowisko do komputerowej oceny postawy ciała, techniką mory projekcyjnej – Posturometr M. Wyniki. Wyniki badań opracowano graficznie. Przedstawiono przebieg zmian średnich wartości kąta koślawości lub szpotawości palca piątego lewej i prawej stopy płci żeńskiej i męskiej na tle zmian obojga płci. Stwierdzenia Kąt koślawości palca V obu stóp u kobiet nie przekracza 1, u mężczyzn 1,5 stopnia. Kąt szpotawości u kobiet i mężczyzn wykazuje nieistotną statystycznie tendencję rosnącą z okresem względnej stagnacji w wieku 12-14 lat. Key words: angle of varus and valgus finger V. Summary Introduction contemporary and generally practiced lifestyle gradually reduces the physical effort for the sedentary model of leisure. Disruptive hypokinetic and static loads is reflected in the joints of the spine, shoulder, hip and foot, resulting in morphological abnormalities of the whole organism, because these changes with regards to the unity of the morpho-functional the entire locomotor system are not limited only to local changes. Aim. Determination of the angle of Varus or valgus finger five feet in load conditions the weight of its own men and women between the ages of 4 to 18 years. Material and methods. The studies covered the population of 9804 women and 8699 men aged from 4 to 18 years of age, with a random sample of kindergartens and schools in the region of Warmia-Mazury. The research methodology involved the measurement of the angle of varus or valgus of the fifth finger of the foot. To evaluate the position was used to evaluate computer posture, moire technique-screening Posturometr M. The results. The results of the tests have been developed graphically. Describes the process of change of the angle values valgus or varus fifth finger left and right feet female and male on the background of the changes in both sexes. Determine the angle of the valgus finger V both feet in women does not exceed 1, men 1.5 degree. The angle of the varus on men and women shows a statistically insignificant trend growing out of a period of relative stagnation at the age of 12-14 years.